Biocatalytic functionalization of bio-sourced terpenes for pharmacological and biocontrol applications - Rodriguez Mosheim, Juan (CCSD, 2024)
The aim of this interdisciplinary thesis was to explore the functionalization of terpenes through enzymatic catalysis for the creation of new compounds of interest, with particular emphasis on the use of lipases in the synthesis of new terpenoid esters. The research involved a series of diverse approaches, starting with the use of simple monoterpenoids to establish optimal reaction conditions. Using the lipase B from Candida antarctica, it was possible to introduce alkyl chains onto monoterpenoids such as geraniol and perillyl alcohol, and also to break new ground by synthesizing previously unproduced terpenoid ketoesters.The work was then extended to sesquiterpene lactones (LST) present in chicory grown in the Hauts-de-France region, where the acylation method was successfully applied. This step led to the creation of new LST derivatives with excellent yields.The project then extrapolated this methodology to complex chicory root extracts, demonstrating the feasibility of acylating LSTs in these mixtures and revealing new, potentially unknown molecules. In parallel, the study explored other biocatalytic reactions, notably with the production of transaminases and alcohol dehydrogenases, opening up prospects for the production of innovative aminoterpenes.This thesis represents a significant advance in our understanding of the biocatalytic functionalization of terpenes, with the potential to synthesize new high-value derivatives for future applications in pharmaceuticals or as biocontrol agents. Cette thèse interdisciplinaire avait pour objectif d'explorer la fonctionnalisation de terpènes à travers la catalyse enzymatique pour la création de nouveaux composés d'intérêt, en mettant l'accent sur l'utilisation de lipases dans la synthèse de nouveaux esters de terpénoïdes. La recherche a impliqué une série de démarches diverses, débutant avec l'emploi de monoterpénoïdes simples pour établir des conditions réactionnelles optimales. L'utilisation de la lipase B de Candida antarctica CAL-B a permis d'introduire des ...